Transformasi Memori “Air Raja” di Negeri Porto-Haria dari Simbol Konflik menjadi Simbol Perdamaian - Handry Handry (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. This research reveals how conflict over water sources can trigger violence and social fragmentation. The conflicts that occur are not solely due to disputes over water sources but rather are more due to the collective memory constructed by each conflicting party. One such social conflict stemming from collective memory occurred in the community of Porto-Haria Village, Saparua District, Central Maluku Regency. The conflict is related to the memory of